(untitled) (American Journal of Islam and Society, 2011)
Nefissa Naguib’s book is the third in Brill’s Women and Gender series. It is an interdisciplinary study comprising an anthropological discussion, social gender theories, and a geographical discussion. The book is primarily based on anthropological research and presents the stories of eight women from the Palestinian village of Musharafah—and by means of which, it creates a discourse that examines the changes that have taken place in the status of women in Palestinian society, and their functioning following the political and economic changes in Palestinian society in general, and in Musharafah in particular. Water is the connecting thread between the stories of the eight women and the analysis of their social functioning in the village. The extensive preface to the book is part of a long theoretical introduction, in which the author explains that “It is a story about how water is an endlessly evolving enactment of gender, family and community relationships” (1). She reviews the aims of the book in general, provides a general description of the village and its women, and discusses terms—such as “society of women”—which she will use extensively in the book. The second part of the theoretical introduction, entitled “The Women and Their Stories,” describes the way of life that is a backdrop for the women’s stories, and the importance of water as a component in each story. The book is comprised of two parts. Part 1, “About Musharafah,” includes the first two chapters, which also constitute a theoretical review, and serve as the basis for the anthropological study and analysis in Part 2 ...